Aspirin therapy on prophylactic anticoagulation for patients hospitalized with COVID‐19: a propensity score‐matched cohort analysis of the HOPE‐COVID‐19 registry - Santoro, Francesco; Núñez‐Gil, Ivan J.; Vitale, Enrica; Viana‐Llamas, María C.; Romero, Rodolfo; Maroun Eid, Charbel; Feltes Guzman, Gisela; Becerra‐Muñoz, Victor Manuel; Fernández Rozas, Inmaculada; Uribarri, Aitor; Alfonso‐Rodriguez, Emilio; García Aguado, Marcos; et al. (Journal of the American Heart Association, 2022)
Background - - COVID‐19 is an infectious illness, featured by an increased risk of thromboembolism. However, no standard antithrombotic therapy is currently recommended for patients hospitalized with COVID‐19. The aim of this study was to evaluate safety and efficacy of additional therapy with aspirin over prophylactic anticoagulation (PAC) in patients hospitalized with COVID‐19 and its impact on survival. - - Methods and Results - - A total of 8168 patients hospitalized for COVID‐19 were enrolled in a multicenter‐international prospective registry (HOPE COVID‐19). Clinical data and in‐hospital complications, including mortality, were recorded. Study population included patients treated with PAC or with PAC and aspirin. A comparison of clinical outcomes between patients treated with PAC versus PAC and aspirin was performed using an adjusted analysis with propensity score matching. Of 7824 patients with complete data, 360 (4.6%) received PAC and aspirin and 2949 (37.6%) PAC. Propensity‐score matching yielded 298 patients from each group. In the propensity score‐matched population, cumulative incidence of in‐hospital mortality was lower in patients treated with PAC and aspirin versus PAC (15% versus 21%, Log Rank P=0.01). At multivariable analysis in propensity matched population of patients with COVID‐19, including age, sex, hypertension, diabetes, kidney failure, and invasive ventilation, aspirin treatment was associated with lower risk of in‐hospital mortality (hazard ratio [HR], 0.62; [95% CI 0.42-0.92], P=0.018). - - Conclusions - - Combination PAC and aspirin was associated with lower mortality risk among patients hospitalized with COVID‐19 in a propensity score matched population compared to PAC alone.